The Lord Will Reveal the Lord: God’s Invisibility and Jesus’ Visibility in 1 Timothy - Wenkel, David H. (Horizons in biblical theology, 2017)
The first pastoral epistle to Timothy follows a relatively traditional Jewish doctrine in the context of second temple Judaism: God is one “whom no one has ever seen or can see” (1 Timothy 6:16). This parallels a statement in chapter one in which God is described as “invisible” (1 Timothy 1:17). In both statements, the invisibility of God is contrasted with the visible quality of Jesus’ spiritual power or his second appearing. This paper argues that the Jewish monotheistic doctrine of God has been developed in a proto-Trinitarian manner by utilizing the qualities of invisibility and visibility.